2012
DOI: 10.1128/aem.02069-12
|View full text |Cite
|
Sign up to set email alerts
|

Seasonal Variations of Indoor Microbial Exposures and Their Relation to Temperature, Relative Humidity, and Air Exchange Rate

Abstract: . Concentrations of fungi were predominately higher outdoors than indoors, whereas bacteria, endotoxin, and inhalable dust concentrations were highest indoors. Bacteria and endotoxin correlated with the mass of inhalable dust and number of particles. Temperature and air exchange rates were positively associated with fungi and N-acetyl-beta-D-glucosaminidase and negatively with bacteria and the total inflammatory potential. Although temperature, relative humidity, and air exchange rates were significantly assoc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

24
185
0
2

Year Published

2015
2015
2024
2024

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 237 publications
(211 citation statements)
references
References 56 publications
24
185
0
2
Order By: Relevance
“…Frankel et al (2012) also observed a distinct seasonal variation in bioaerosol levels. In our study, since the sampling was carried out during different seasons, a one way ANOVA was applied to determine the impact of season upon bacterial and fungal levels in indoor environments.…”
Section: Seasonal Variation In Bioaerosol Levelsmentioning
confidence: 77%
“…Frankel et al (2012) also observed a distinct seasonal variation in bioaerosol levels. In our study, since the sampling was carried out during different seasons, a one way ANOVA was applied to determine the impact of season upon bacterial and fungal levels in indoor environments.…”
Section: Seasonal Variation In Bioaerosol Levelsmentioning
confidence: 77%
“…In the same period, PM10 concentrations strongly decreased during rain events. To explain this phenomenon, several hypotheses were proposed: 1) raindrops carried the microorganisms from higher altitude environments to ground-level environments; 2) the rainclouds decreased UV irradiation, which prevented the inactivation of culturable bioaerosols; 3) the splashing effects of raindrops propelled microorganisms on the ground into the surrounding air environment; and 4) the increased relative humidity during rain enhanced the sampling efficiency of the biosampler for culturable bioaerosols and might have generated adequate environments for the growth of microorganisms (Pasanen et al, 1991;Frankel et al, 2012;Heo et al, 2014). In the current study, we tried to test and evaluate each hypothesis by measuring bioaerosols in various environmental conditions.…”
Section: Introductionmentioning
confidence: 99%
“…In previous studies of indoor air quality conducted in Chicago homes, culturable bacteria were highest in summer and fall (Moschandreas et al, 2003), whereas in Finland, only a slight yet significant difference was observed between summer and winter bacterial levels (Reponen et al, 1992). However, other studies in homes have shown a large decline from spring to summer, an increase in fall, followed by a decrease toward winter (Frankel et al, 2012). These discrepancies might be caused by other factors, which can influence CAB concentrations, rather than by seasonal changes themselves.…”
Section: Discussionmentioning
confidence: 78%